HEUTAGOGY IN THE COURSE OF PESANTREN EDUCATION (CASE STUDY AT PESANTREN SALAF AL-LUQMANIYYAH) - Munganatl Khoeriyah (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2019)
Pesantren, the Islamic boarding school, is the oldest Islamic education in Indonesia and is constantly undergoing changes from time to time. This research uses the qualitative approach. This study aims to describe the application of the heutagogy method in the growth of pesantren education. The results of this study indicate that the Al-Luqmaniyyah salaf Boarding School has already applied the heutagogy learning method, it means that pesantren education precedes the Westerners in terms of its utilization. Through the study and discussion of Kitab Kuning (yellow-colored textbooks about Islamic knowledge), students determine their systems, study materials, and problems to find a solution. Sources of learning for students are not only limited by the Kitab Kuning, but students can also have access through the internet, online books and applications with trusted sources. PSDS is responsible for managing the talents and interests of the santri (a term used in Pesantren to call an apprentice), as well as training santri skills by making films, recording, creativity, writing, making advertisements, making interesting contents on social media. LP2M Al-Luqmaniyyah with its various divisions is required to channel and facilitate what the community needs from the students as they can also learn from the community it self. Keywords: Heutagogy, Islamic boarding school education.